Political, leaflet-distributor groups in Transcarpathia during the Hungarian Revolution of 1956 - Natalia Varadi; Вароді Наталія; Váradi Natália (Accent Graphics Communications & Publishing, 2019)
Abstract. The mournful and bloody Revolution and War of Independence of 1956 demonstrated the existence of Hungarian unity and cooperation even in spite of the numerous hardships and artificially drawn borders. It also proved that there is a common homeland in people’s hearts, for which those who consider themselves Hungarian hold together within and beyond the borders even if the political powers take revenge on it.
Keywords: Hungarian revolution of 1956; Soviet Union; Transcarpathia